Effects of Medium pH and Preconditioning Treatment on Protein Adsorption on 45S5 Bioactive Glass Surfaces - Höhn, Sarah; Zheng, Kai; Romeis, Stefan; Brehl, Martin; Peukert, Wolfgang; de Ligny, Dominique; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Advanced Materials Interfaces, 2020)
Protein adsorption on 45S5 bioactive glass (BG, Bioglass) surfaces influences the biocompatibility of Bioglass and the cellular response to the material. The medium pH greatly affects protein adsorption behavior. However, the influence of pH variation on protein adsorption on Bioglass has not been investigated in detail before, although an acidifying pH has been observed in fractured or injured bone tissues. This study investigates how the medium pH (pH 7, 5, and 2) affects protein (serum albumin) adsorption on Bioglass with or without preconditioning in simulated body fluid (SBF). The results show that Bioglass can adsorb a larger amount of bovine serum albumin (BSA) than bioinert glasses at all tested pHs. The BSA adsorption on Bioglass surfaces is pH-dependent and a larger amount of adsorbed BSA is observed at lower pH (5 and 2). After preconditioning, BSA adsorption is significantly enhanced. However, the trend of pH-dependent adsorption is attenuated. No significant difference in BSA adsorption is observed at different pHs after preconditioning. The results reveal for the first time the influence of medium pH on protein adsorption on Bioglass with or without preconditioning treatment in SBF, which provides useful information for developing Bioglass based biomedical devices that will be in contact with protein-containing physiological fluids during applications.
CRIS-Team Scopus Importer:2020-05-29
Keywords: 45S5 Bioglass; bovine serum albumin; pH influence; preconditioning; surface reactivity